Nitrogen-Doped Carbon Dots Induced Enhancement in CO2 Sensing Response From ZnO–Porous Silicon Hybrid Structure - Ramos-Ramón, Jesús A.; Bogireddy, Naveen K. R.; Giles Vieyra, Jorge Arturo; Karthik, Tangirala V. K.; Agarwal, Vivechana (Frontiers in Chemistry, 2020)
In this study, we report a simple method for the fabrication of carbon dots sensitized zinc oxide-porous silicon (ZnO-pSi) hybrid structures for carbon dioxide (CO2) sensing. A micro-/nanostructured layer of ZnO is formed over electrochemically prepared pSi substrates using a simple chemical precipitation method. The hybrid structure was structurally and optically characterized using scanning electron microscopy, X-ray diffraction, fluorescence, and cathodoluminescence after the incorporation of hydrothermally prepared nitrogen-doped carbon dots (NCDs) by drop-casting. With respect to the control sample, although all the devices show an enhancement in the sensing response in the presence of NCDs, the optimal concentration shows an increase of ~37 % at an operating temperature of 200 °C and a response time <30 s. The increment in the CO2 sensing response, upon the addition of NCDs, is attributed to an increase in CO2-oxygen species reactions on the ZnO surface due to an increment in the free electron density at the metal-semiconductor type junction of NCDs clusters and ZnO micro-/nanorods. A significant increase in the sensing response (~24 %) at low operating temperature (100 °C) opens the possibility of developing VLSI integrable, low operational cost gas sensors with easy fabrication methods and low-cost materials.